KARAKTERISTIK KONSENTRAT PROTEIN TERIPANG PASIR (Holothuria scabra J.) DENGAN BAHAN PENGEKSTRAK ASETON - Karnila, Rahman; Astawan, Made; Sukarno, Sukarno; Wresdiyati, Tutik (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
Sea cucumber (Holothuria scabra J.) is a fishery that has a nutrientcontent and high economic value. This study aims to know: (1) nutrient content(proximate) sea cucumber fresh meat, (2) the yield of protein concentratemanufacture of sea cucumbers, (3) nutrient content of sea cucumber proteinconcentrate, and (4) total amino acid content of protein concentrates of seacucumber.Penelitian in five stages of the experiment: (1) preparation of meat freshsea cucumbers, (2) analysis of nutrient content (proximate) sea cucumber freshmeat, (3) the analysis of protein concentrate yield of seacucumbers, (4) analysis ofnutrient content (proximate) protein concentrate sea cucumbers, and (5) analysisof total amino acid content of sea cucumber protein concentrate. The resultsshowed nutrient content (proximate) sand sea cucumber fresh meat that is 87.03%water (bb): 76.64% protein (bk); 4.16% fat (bk), 14.34% ash (bk), and 4 , 93%carbohydrate (bk). The average yield produced in the manufacture of seacucumber protein concentrate was 9.87%. While the nutrient content (proximate)sea cucumber protein concentrate that is 8.97% water, 66.07% protein, 0.89% fat;11.53% ash, and 12.54% carbohydrate. The highest amino acid content in seacucumber protein concentrate is a proline (5.17%) and glutamic acid (3.23%).